2015
DOI: 10.17015/ejbe.2015.016.03
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Productivity and Profitability of Indian Banking Sector: A Comparative Study

Abstract: The purpose of this paper is to discuss the different determinants of productivity and profitability of banks functioning in India. The performance of public and private sector banks in terms of productivity and profitability is being assessed in two different time periods (2003-04 to 2008-09 and 2009-10 to 2013-2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…Therefore, the higher the net interest margin, the more efficient banks are thus productivity may increase. Narwal and Pathneja (2015) pointed out the diversification of activities was more essential to productivity than net interest margin which stated that diversification and net interest margin may lead the banks towards more productivity.…”
Section: Productivitymentioning
confidence: 99%
“…Therefore, the higher the net interest margin, the more efficient banks are thus productivity may increase. Narwal and Pathneja (2015) pointed out the diversification of activities was more essential to productivity than net interest margin which stated that diversification and net interest margin may lead the banks towards more productivity.…”
Section: Productivitymentioning
confidence: 99%
“…Stochastic frontier production function approach (SFPFA) and data envelopment analysis (DEA) are the two main techniques which can be used to estimate the technical efficiency (TE) of firms/industries and other sectors of the economy (Aigner, Lovell & Schmidt, 1977;Meeusen & Van den Broeck, 1977;Chavas & Aliber, 1993;Kumbhakar & Lovell, 2003;Rajesh, 2007;Faruq & Yi, 2010;Akpan et al, 2012;Pattnayak & Chadha, 2013;Kumar & Arora, 2012;Hamjah, 2014;Zhou, 2014;Mahajan, Nauriyal & Singh, 2014;Debnath & Sabastian, 2014;Bhatia & Mahendru, 2015;Munisamy, Fon & Khin, 2015;Sahu, 2015;Ng'ombe & Kalinda, 2015;Narwal & Pathneja, 2015;Ikram, Su & Sadiq, 2016); Okoye et al, 2016;Kea, Li & Pich, 2016;Vu, 2016;Fahmy-Abdullah et al, 2017;Gebresilassie, & Nyatanga, 2017;Singh, Narayanan & Sharma, 2018;Singh, Narayanan & Sharma, 2019). Efficiency is defined as the best allocation of resources to achieve the highest level of output (Bhatia & Mahendru, 2015).…”
Section: Theoretical Framework Of Stochastic Frontier Production Funcmentioning
confidence: 99%
“…It observes that TE of foreign firms in five industries (i.e., chemical, machinery, electronics industry, and transport) are appeared higher than Indian firms. Narwal and Pathneja (2015) have assessed the productivity and profitability of the banking system in India using the DEA method. It witnessed that private sector banks have more productivity than public sector banks.…”
Section: Review Of Existing Literaturementioning
confidence: 99%
“…Furthermore, within the framework of regulations and supervision, they pointed out that competition is effective in converging the profits to the equilibrium point in the long run. Narwal and Pathneja (2015) analyzed the determinants of Indian's banks profitability during 2003-2014. Fixed effects panel data results showed that both diversification and spread were positively related too banks' profitability.…”
Section: Literaturementioning
confidence: 99%